2016
DOI: 10.1038/ncomms11688
|View full text |Cite
|
Sign up to set email alerts
|

Rebalancing gene haploinsufficiency in vivo by targeting chromatin

Abstract: Congenital heart disease (CHD) affects eight out of 1,000 live births and is a major social and health-care burden. A common genetic cause of CHD is the 22q11.2 deletion, which is the basis of the homonymous deletion syndrome (22q11.2DS), also known as DiGeorge syndrome. Most of its clinical spectrum is caused by haploinsufficiency of Tbx1, a gene encoding a T-box transcription factor. Here we show that Tbx1 positively regulates monomethylation of histone 3 lysine 4 (H3K4me1) through interaction with and recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 39 publications
7
84
0
Order By: Relevance
“…For example, T-box factors including T-BET and T were shown to physically interact with RBBP5, a member of the H3K4 methyltransferase complex and to control H3K4me2 at target genes [7]. Recently, TBX1 was reported to physically interact with histone methyltransferase enzymes, including MLL3, and Tbx1 knockdown resulted in a decrease in H3K4me1 levels at a subset of TBX1 binding sites [53]. Furthermore, a physical interaction between T-BET and p300 has previously been shown [51], although unlike in our study, the authors did not show a functional requirement for T-BET in the recruitment of H3K27ac to T-BET target sites.…”
Section: Discussionmentioning
confidence: 99%
“…For example, T-box factors including T-BET and T were shown to physically interact with RBBP5, a member of the H3K4 methyltransferase complex and to control H3K4me2 at target genes [7]. Recently, TBX1 was reported to physically interact with histone methyltransferase enzymes, including MLL3, and Tbx1 knockdown resulted in a decrease in H3K4me1 levels at a subset of TBX1 binding sites [53]. Furthermore, a physical interaction between T-BET and p300 has previously been shown [51], although unlike in our study, the authors did not show a functional requirement for T-BET in the recruitment of H3K27ac to T-BET target sites.…”
Section: Discussionmentioning
confidence: 99%
“…Del22q11 includes the T-Box transcription factor TBX1 , and haploinsufficiency for TBX1 underlies the cardio-pharyngeal phenotype 32–34 . Recent work in mice haploinsufficient for Tbx1 delineates regulation of H3K4me1 enrichment, providing an intriguing link between TBX1 and chromatin remodeling in CHD 35 . Other CHD-associated CNVs that are well characterized include del8p23, which includes the cardiac transcription factor GATA4 and manifests with a range of CHD along with developmental delay 36 ; del7q11, the cause of William Syndrome, wherein the cardiac disease consists of supravalvar aortic and pulmonary stenosis and results from haploinsufficiency for Elastin 37, 38 ; del 11q24-25 resulting in Jacobsen Syndrome 39, 40 .…”
Section: Established Genetic Contributions To Chdmentioning
confidence: 99%
“…We speculated that W118R in ENU706 mice might also have a gain-of-function as other T-box mutations. More interestingly, recent study indicated that it also binds to chromatin that may function epigenetically [36]. Another study proposed that cortical development was regulated by mesodermal expression of Tbx1 [37].…”
Section: Discussionmentioning
confidence: 99%